A new approach to characterize the performance of heavy oil recovery due to various gas injection. (February 2018) - Rostami, Behzad; Pourafshary, Peyman; Fathollahi, Alireza; Yassin, Mahmood Reza; Hassani, Kamran; Khosravi, Maryam; Mohammadifard, Mohammad; Dangkooban, Ahmad
Highlights: Effects of CO2, N2 and HC injection on oil recovery were investigated. Oil bypassing and trapping caused recovery reduction at rates higher than critical. IFT reduction due to CO2 injection may not improve oil recovery drastically. A new dimensionless number was proposed to evaluate the performance of GAGD. Oil viscosity reduction and oil swelling are the dominant mechanisms. Abstract: The performance of CO2 injection into a semi-heavy oil reservoir was investigated at reservoir conditions, using highly permeable sandstone in a complete series of PVT tests and coreflooding experiments. Analysis of involved parameters such as: injection rate, injectant type and reservoir pressure were also considered. Oil viscosity reduction and oil swelling are the most influential mechanisms of enhanced oil recovery in this process. The results demonstrated that CO2 injection would decrease the interfacial tension for the high permeable medium in the absence of capillarity, but this reduction may not improve the recovery drastically. One of the main important aspects of this work is the introduction of a new empirical combined dimensionless group (dissolution number, Ndis ) that helps prediction of oil recovery in any other heavy oil reservoir with high permeability of porous media. In this case, a more precise analysis could be performed by applying the dissolution number instead of capillary and/or Bond number.